Ecumenical Agencies as Partners for Development in South Africa - Le Bruyns, C (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
This article explores briefly the extent to which ecumenical bodies could make good partners for the development agenda within an African framework of nation-building. To this end, three questions are posed to assist in this engagement with the topic. These questions imply various avenues that demand attention, reflection and action by the contemporary ecumenical community and public theology in their ecclesial and academic participation in development and nation-building.